ECCD-induced sawtooth crashes at W7-X. (9th September 2020) - Zanini, M.; Laqua, H.P.; Thomsen, H.; Stange, T.; Brandt, C.; Braune, H.; Brunner, K.J.; Fuchert, G.; Hirsch, M.; Knauer, J.; Höfel, U.; Marsen, S.; et al.
Abstract: The optimised superconducting stellarator W7-X generates its rotational transform by means of external coils, therefore no toroidal current is necessary for plasma confinement. Electron cyclotron current drive experiments were conducted for strikeline control and safe divertor operation. During current drive experiments periodic and repetitive crashes of the central electron temperature, similar to sawtooth crashes in tokamaks, were detected. Measurements from soft x-ray tomography and electron cyclotron emission show that the crashes are preceded by weak oscillating precursors and a displacement of the plasma core, consistent with a ( m, n ) = (1, 1) mode. The displacement occurs within 100 μ s, followed by expulsion and redistribution of the core into the external part of the plasma. Two types of crashes, with different frequencies and amplitudes are detected in the experimental program. For these non-stationary parameters a strong dependence on the toroidal current is found. A 1-D heuristic model for current diffusion is proposed as a first step to explain the characteristic crash time. Initial results show that the modelled current diffusion timescale is consistent with the initial crash frequency and that the toroidal current rise shifts the position where the instability is triggered, resulting in larger crash amplitudes.